Exploring online infaq intentions of young Muslim - Ikawati, Retty; Afriadi, Fiqih; Fitriyani, Yeny; Ash Shidiqie, Jannahar Saddam; Lidasan, Mussolini Sinsuat (Asian Journal of Islamic Management (AJIM), 2024)
Purpose – This study aims to analyze the intention of the young Muslim generation in paying infaq using online platforms. Methodology – The respondents in this study were 320 young Muslims who had previously made infaq payments through online platforms. The research framework applied was an extended unified theory of acceptance and use of technology (UTAUT) model to predict the intention to use new technology. Structural equation modeling (SEM) techniques to assess the validity, reliability, and relationships between various latent variables.Findings – The results of the data analysis show that performance expectations, social influence, infaq literacy, and habits have a significant influence on the intention to pay infaq through online platforms. In addition, habits and intention to pay donations online also influence usage behavior in paying donations via online platforms. Implications – Based on these findings, it is recommended that the Amil Zakat Infaq and Sedekah Agency (BAZNAS) collaborate with profit-oriented and non-profit social organizations in Indonesia. This collaboration is expected to improve online infaq services and expand the reach of community participation, in line with the increasing intention in and habit of using online platforms to pay infaq.Originality – This study uniquely focuses on the young Muslim generation's behavior in using online platforms for infaq, an area not extensively explored in previous research. By employing Structural Equation Modeling (SEM), it offers a comprehensive analysis of both direct and indirect effects, providing actionable insights for enhancing online donation platforms.